2017
DOI: 10.22271/ortho.2017.v3.i1i.83
|View full text |Cite
|
Sign up to set email alerts
|

Management of floating shoulder injury with dual surgical approach

Abstract: The aesthetic appearance of the thumb hasn't been analysed to a similar extent as thumb function which would aid during reconstructive surgeries of the thumb and first web space and analyse its outcome. The purpose of this study is to determine the relative length, girth, nail width of thumb with respect to the index finger and intermetacarpal distance. Measurement of the 1 st web space arc radius has been done to tackle the problem of webbing which is not addressed by IMD and palmar abduction angles. A total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…This reduces the risk of non-union, alleviates tension on the brachial plexus, restores normal anatomical relationships and ensures restoration of normal shoulder function. 6,26 They came out with a concept that fracture of glenoid neck will indirectly reduce and stabilize as a result of clavicle fixation. However, if significant displacement of glenoid neck persists, it should be reduced and fixed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This reduces the risk of non-union, alleviates tension on the brachial plexus, restores normal anatomical relationships and ensures restoration of normal shoulder function. 6,26 They came out with a concept that fracture of glenoid neck will indirectly reduce and stabilize as a result of clavicle fixation. However, if significant displacement of glenoid neck persists, it should be reduced and fixed.…”
Section: Discussionmentioning
confidence: 99%
“…double disruption), the integrity of the superior shoulder suspensory complex is breached and a potentially anatomically unstable situation is created. 6 In such situation the weight of the arm and the muscles acting on the humerus pull the glenoid fragment distally and anteromedially which results into drooping of shoulder followed by nonunion, malunion, brachial plexopathy, limited range of motion, weakness in abduction and subacromial impingement. 7 Williams et al in a cadaveric study observed that in ipsilateral glenoid neck and clavicular fractures, instability of the glenoid segment occurred only if the coracoacromial and acromioclavicular ligaments were divided.…”
Section: Anatomical Considerationsmentioning
confidence: 99%